Lidocaine and Pinacidil Added to Blood versus Crystalloid Cardioplegic Solutions: Study in Isolated Hearts - Carmo,Helison Pereira do (2018)
Abstract Objective: The present study aimed the functional recovery evaluation after long term of cardiac arrest induced by Custodiol (crystalloid-based) versus del Nido (blood-based) solutions, both added lidocaine and pinacidil as cardioplegic agents. Experiments were performed in isolated rat heart perfusion models. Methods: Male rat heart perfusions, according to Langendorff technique, were induced to cause 3 hours of cardiac arrest with a single dose. The hearts were assigned to one of the following three groups: (I) control; (II) Custodiol-LP; and (III) del Nido-LP. They were evaluated after ischemia throughout 90 minutes of reperfusion. Left ventricular contractility function was reported as percentage of recovery, expressed by developed pressure, maximum dP/dt, minimum dP/dt, and rate pressure product variables. In addition, coronary resistance and myocardial injury marker by alpha-fodrin degradation were also evaluated. Results: At 90 minutes of reperfusion, both solutions had superior left ventricular contractile recovery function than the control group. Del Nido-LP was superior to Custodiol-LP in maximum dP/dt (46%±8 vs. 67%±7, P<0.05) and minimum dP/dt (31%±4 vs. 51%±9, P<0.05) variables. Coronary resistance was lower in del Nido-LP group than in Custodiol-LP (395%±50 vs. 307%±13, P<0.05), as well as alpha-fodrin degradation, with lower levels in del Nido-LP group (P<0.05). Conclusion: Del Nido-LP cardioplegia showed higher functional recovery after 3 hours of ischemia. The analysis of alpha-fodrin degradation showed del Nido-LP solution provided greater protection against myocardial ischemia and reperfusion (IR) in this experimental model.